Healthy Eating: Nutrition and Diabetes - Linda B. Bobroff; Jennifer Hillan; Emily Minton (EDIS)
A healthy diet, along with exercise and medication, can help control diabetes and reduce the risk of complications. A healthy lifestyle also helps reduce the chances of developing diabetes for those who are at high risk. For a healthy diet, follow these tips. This revised 3-page fact sheet was written by Linda B. Bobroff, Jennifer Hillan, and Emily Minton, and published by the UF Department of Family, Youth and Community Sciences, February 2015. (Photo:iStock/Thinkstock.com)